PENDAMPINGAN PROMOSI DESTINASI WISATA DESA AIK BUKAQ SEBAGAI DESA WISATA DI KABUPATEN LOMBOK TENGAH - Aulia, Maulidya Rahmi; Pertiwi, Linda; Wijaya, Inta Hikna; Hashifa, Alya Maureen; Setiawan, Dawam; Hemawan, Rizal Hendri; Jorgi, Tomas; Bagaskara, Lalu Satria; Adawiyah, Rabiatul; Risma, Ni Kadek Anggitha Yulia (Jurnal Wicara, 2023)
Aik Bukaq Village is a village in North Batukliang District, Central Lombok Regency. The village has abundant natural wealth and tourist destinations. Aik Bukaq Village has several tourist destinations including the Aik Bukaq swimming pool, Tereng Kuning tourism, and a reservoir whose water is sourced directly from mountain springs. The KKN program aims to do community service in solving village problems in the field of tourism, namely promotions such as snacks or natural tourist destinations. The outputs expected from the KKN program are: 1) Leaflets related to Appropriate Technology applied; 2) Scientific article entitled "Assisting in the Creative Promotion of Aik Bukaq Village Tourism Destinations as a Tourism Village in Central Lombok Regency"; 3) Mass media publication, 4) A 10-minute documentary video uploaded to social media accounts such as Instagram and YouTube, 5) Video products to promote Aik Bukaq Village tourism. The proposed Village Community Empowerment KKN program includes tourism promotion, tourism awareness outreach, health outreach about stunting, teaching, village office pickets, and games. The KKN program will be carried out in June - August 2023 by a group of 10 people.